Implementation of One Day One Story Program to Develop Literacy Skills of Elementary School Students - Daryanti; Wachid Bambang Suharto, Abdul (International Proceedings of Nusantara Raya, 2024)
Literacy covers many aspects, not only reading and writing skills, but also includes the ability to understand information in a logical and critical way. Based on the results of observations in class III of SD Negeri 1 Cilangkap, students' ability to understand information is still low, this can be seen when students work on questions, some do not understand the meaning of the question. So to answer, there needs to be help from the teacher to understand the questions being worked on. One way to develop literacy skills among children is to use the storytelling method. This method can not only increase their interest in reading, but also improve verbal language skills, overall reading comprehension, and writing skills. The formulation of the problem in this study is how the implementation of the one-day-one-story program can develop students' literacy skills at the elementary school level. The purpose of this study was to analyze the extent to which the program contributed to improving student literacy. This study uses a qualitative descriptive approach, with data collection methods used including direct observation, interviews, and documentation from students who participated in the one-day-one-story program . The results showed an increase in children's verbal abilities, creativity, and the emergence of ideas and concepts from students. This is reflected in the students' ability to tell stories well and the interaction between students who ask each other questions to dig deeper into information.